EUROPEAN UNION CYBER SECURITY IN DEALING WITH THE THREAT OF AI-CYBERCRIMES: LESSONS FOR INDONESIA - Hussin, Mutia Hariati; Salwa Prilia Ginano, Mutia Hariati (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
This paper discusses the evolution of crimes related to artificial intelligence technology, responses, and mitigation initiatives the European Union took. This study aims to provide information about the early development of AI and how it is used as a tool for cybercrime called Deepfake. The qualitative research methodology will collect data for this study to gain information from various sources, such as pertinent books, news articles, and journals. The authors found that artificial intelligence, or AI, has become essential to daily life. While it has provided benefits, it also created new problems, such as artificial child pornography and porn being exploited for various reasons. This becomes a significant international risk to cybersecurity. The sensitivity and intricacy of this topic call for coordinated efforts from many different parties. In response to this problem, the European Union has formed solutions that Indonesia could learn from.